Personality Traits and Deception Detection Ability Among College Students with Primary Psychopathic Traits - Malmstrom, Megan (2015)
Because psychopaths are exceptionally good at deceiving others, researchers have proposed that this population of individuals may be more likely than the average person to detect deception. However, previous research has provided mixed results on the ability of individuals with psychopathic traits to detect deception at a greater level than chance. The inconclusive results on this topic have warranted future research on examining sex differences and personality traits that are attributed to individuals with psychopathy that may aid their ability to detect deception at a higher level than others. The current study tested 133 San Jose State University undergraduates by having them indicate whether individuals in 10 different video clips were lying or telling the truth. Participants’ psychopathic tendencies were measured using the Levenson Self-Report Psychopathy scale (LSRP) and their personality traits were measured using the Big Five Inventory (BFI). A Fisher’s r to z transformation was conducted to test Hypothesis 1, that sex would moderate the relationship between deception detection accuracy and primary psychopathic traits. However, our analyses revealed no moderating effect by sex. A one-tailed bivariate correlation was also performed to test Hypothesis 2, which stated that low scores on the BFI for Agreeableness and Conscientiousness would be correlated with higher deception detection accuracy. No significant relationships were found. However, non-significant results displayed non-linear relationships between Agreeableness, Conscientiousness and detection accuracy